Government Strategy in Reducing Stunting Rate for the People of North Labuhanbatu Regency towards Zero Stunting - Putra, Andriansyah; Muin, H. M. Iqbal Abdul (LP2M INSURI Ponorogo, 2024)
This problem is one of the problems that has an impact on the development and improvement of the younger generation. The absence of energy and protein in a long enough period of time will cause inhibition of growth and development in infants. This research aims to find out the strategies implemented by the North Labuhanbatu Regency government in the process of reducing stunting rates and how to overcome them. This research uses a qualitative approach with descriptive research type. Research data was obtained from interviews and observations. The data analysis carried out was taken from several stunting cases that have occurred and looked at the social situation and conditions in the field. The results of this research show that there are still many cases of stunting occurring in North Labuhanbatu Regency, especially among toddlers, pregnant women, postpartum and breastfeeding mothers, prospective brides, and grooms. The main causes of stunting are nutritional, health and environmental disorders. This has become the concern of the North Labuhanbatu Regency government in the process of targeting a reduction in the stunting rate towards zero stunting by 2024. Apart from that, the government will carry out eight convergence actions to reduce stunting in each district/city.